The interrelationship of helicase and nuclease domains during DNA translocation by the molecular motor EcoR124I - Sisáková, Eva; Weiserová, Marie; Dekker, Cees; Seidel, Ralf; Szczelkun, Mark D (Journal of molecular biology, 2008)
The type I restriction-modification enzyme EcoR124I comprises three subunits with the stoichiometry HsdR2/HsdM2/HsdS1. The HsdR subunits are archetypical examples of the fusion between nuclease and helicase domains into a single polypeptide, a linkage that is found in a great many other DNA processing enzymes. To explore the interrelationship between these physically linked domains, we examined the DNA translocation properties of EcoR124I complexes in which the HsdR subunits had been mutated in the RecB-like nuclease motif II or III. We found that nuclease mutations can have multiple effects on DNA translocation despite being distinct from the helicase domain. In addition to reductions in DNA cleavage activity, we also observed decreased translocation and ATPase rates, different enzyme populations with different characteristic translocation rates, a tendency to stall during initiation and altered HsdR turnover dynamics. The significance of these observations to our understanding of domain interactions in molecular machines is discussed.
Keywords: Kinetics; endonukleasy; molekulární motory; kinetika; Amino Acid Motifs; Molecular Sequence Data; Escherichia coli; terciární struktura proteinů; Endonucleases; sekvence aminokyselin; Biological Transport; Protein Structure, Tertiary; podjednotky proteinů; Mutagenesis; Biological Assay; Optical Tweezers; Protein Subunits; DNA-helikasy; biotest; DNA Helicases; aminokyselinové motivy; DNA; restrikční endonukleasy typu I; adenosintrifosfatasy; Mutant Proteins; Adenosine Triphosphatases; optická pinzeta; Molecular Motor Proteins; biologický transport; Deoxyribonucleases, Type I Site-Specific; mutantní proteiny; Amino Acid Sequence; mutageneze; molekulární sekvence - údaje